Does social value matter in energy saving behaviors?: Specifying the role of eleven human values on energy saving behaviors and the implications for energy demand policy - Kim, Sohee; Kim, Seoyong (Energy Strategy Reviews, 2024)
Energy saving is a critical factor in addressing the global energy crisis. This study analyzes the role of 11 values (ideology, post-materialism, environmentalism, global citizenship, religiosity, science and technology (S&T) optimism, hedonic value, altruistic value, egoistic value, traditionalism, and openness to change) in energy-saving behavior. This study analyzes social survey data (N = 1571) using variables related to the theory of planned behavior (TPB). Global citizenship, traditionalism, S&T optimism, and environmentalism are important causal factors in energy-saving behaviors. Post-materialism, S&T optimism, and hedonic value significantly moderated the relationship between the TPB variables and energy-saving actions. The results indicate that since values matter, it is necessary to link personal value structures and energy-saving actions to encourage sustainable consumption.
Keywords: Energy savings; Energy-consumption; Energy-saving behavior; Energy-savings; Environmentalism; Global citizenship; Hedonic values; Science and Technology; Theory of Planned Behavior; Value; Energy consumption; Energy-saving behavior; Environmentalism; Value